Factors associated with the utilization and costs of health and social services in frail elderly patients - Kehusmaa Sari; Autti-Rämö Ilona; Helenius Hans; Hinkka Katariina; Valaste Maria; Rissanen Pekka (BMC, 2012)
Abstract Background Universal access is one of the major aims in public health and social care. Services should be provided on the basis of individual needs. However, municipal autonomy and the fragmentation of services may jeopardize universal access and lead to variation between municipalities in the delivery of services. This paper aims to identify patient-level characteristics and municipality-level service patterns that may have an influence on the use and costs of health and social services of frail elderly patients. Methods Hierarchical analysis was applied to estimate the effects of patient and municipality-level variables on services utilization. Results The variation in the use of health care services was entirely due to patient-related variables, whereas in the social services, 9% of the variation was explained by the municipality-level and 91% by the patient-level characteristics. Health-related quality of life explained a major part of variation in the costs of health care services. Those who had reported improvement in their health status during the preceding year were more frequent users of social care services. Low informal support, poor functional status and poor instrumental activities of daily living, living at a residential home, and living alone were associated with higher social services expenditure. Conclusions The results of this study showed municipality-level variation in the utilization of social services, whereas health care services provided for frail elderly people seem to be highly equitable across municipalities. Another important finding was that the utilization of social and health services were connected. Those who reported improvement in their health status during the preceding year were more frequently also using social services. This result suggests that if municipalities continue to limit the provision of support services only for those who are in the highest need, this saving in the social sector may, in the long run, result in increased costs of health care.